Sustainable Marketing: Challenges and Opportunities - Panda, Rajeev Kumar (Indian Journal of Marketing, 2007)
This paper examines sustainable marketing with ethical bases and are discussed that directly relate to sustainability. Sustainable marketing is defined both in European and American front and the relationship with the marketing mix element is also established. The bridge between short-term consumer satisfaction and long term consumer welfare is made. The paper also includes the future of sustainable marketing with both positive and negative aspects. Finally, the marketing system of the world should be shown with great adaptability and responsiveness. The same spirit needs to be applied to sustainable marketing and hopefully, much more progress and prosperity can be achieved in the times to come. The paper concludes with the position that sustainability challenges traditional marketing practice.